Impact of sanctions on trade and economic cooperation between Russia and China - Shvab, Natalia; Štěrbová, Ludmila, 1957-; Tomášek, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis analyses how Western sanctions imposed on Russia in 2014 and 2022 affected trade and economic cooperation between Russia and China. The thesis combines quantitative and qualitative methods: data on macroeconomic indicators and trade flows are complemented by a case study of key energy and infrastructure projects. The results show that sanctions accelerated Russia’s reorientation toward China, especially in the energy sector, while foreign direct investment remained limited. The analysis confirms a growing asymmetry in the relationship, in which Russia becomes economically more dependent on China, whereas integration takes place mainly in trade rather than in investment or technology.
Vedoucí práce: Ludmila Štěrbová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses